Circadian rhythm of cardiac troponin I and its clinical impact on the diagnostic accuracy for acute myocardial infarction. (1st November 2018) - Wildi, K.; Singeisen, H.; Twerenbold, R.; Badertscher, P.; Wussler, D.; Klinkenberg, L.J.J.; Meex, S.J.R.; Nestelberger, T.; Boeddinghaus, J.; Miró, Ò.; Martin-Sanchez, F.J.; Morawiec, B.; et al.
Abstract: Background: High-sensitivity cardiac troponin T (hs-cTnT) blood concentrations were shown to exhibit a diurnal rhythm, characterized by gradually decreasing concentrations throughout daytime, rising concentrations during nighttime and peak concentrations in the morning. We aimed to investigate whether this also applies to (h)s-cTnI assays and whether it would affect diagnostic accuracy for acute myocardial infarction (AMI). Methods: Blood concentrations of cTnI were measured at presentation and after 1 h using four different cTnI assays: three commonly used sensitive (s-cTnI Architect, Ultra and Accu) and one experimental high-sensitivity assay (hs-cTnI Accu) in a prospective multicenter diagnostic study of patients presenting to the emergency department with suspected AMI. These concentrations and their diagnostic accuracy for AMI (quantified by the area under the curve (AUC)) were compared between morning (11 p.m. to 2 p.m.) and evening (2 p.m. to 11 p.m.) presenters. Results: Among 2601 patients, AMI was the final diagnosis in 17.6% of patients. Concentrations of (h)s-cTnI as measured using all four assays were comparable in patients presenting in the morning versus patients presenting in the evening. Diagnostic accuracy for AMI of all four (h)s-cTnI assays were high and comparable between patients presenting in the morning versus presenting in the evening (AUC at presentation: 0.90 vs 0.93 for s-cTnI Architect; 0.91 vs 0.94 for s-cTnI Ultra; 0.89 vs 0.94 for s-cTnI Accu; 0.91 vs 0.94 for hs-cTnI Accu). Conclusions: Cardiac TnI does not seem to express a diurnal rhythm. Diagnostic accuracy for AMI is very high and does not differ with time of presentation. Clinical trial registration: NCT00470587, http://clinicaltrials.gov/show/NCT00470587 Highlights: There is no difference in cTnI concentrations between patients presenting in the morning and in the evening in all assessed diagnostic groups. The diagnostic accuracy for AMI is very high and similar for all patients, irrespective of the time of presentation. In the important subgroup of early presenting patients, the same results could be shown. These findings indicate that (h)s-cTnI expresses no circadian rhythm and is safe in use at all time of the day.